1996
DOI: 10.1097/00004032-199607000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Results of Selective Cytogenetic Monitoring of Chernobyl Accident Victims in the Ukraine

Abstract: Selective cytogenetic monitoring of the highest priority groups of Chernobyl disaster victims has been carried out since 1987. In 1992-1993, 125 liquidators (irradiated mainly in 1986) and 42 persons recovering from acute radiation sickness of the second and third degrees of severity were examined. Cytogenetic effects (an elevated level of unstable as well as stable markers of radiation exposure) were found in all groups, which showed a positive correlation with the initial degree of irradiation severity even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…However, a history of smoking was observed to have some effects on the chromosome translocation frequency [24]; follow-up studies of exposed subjects are needed to characterize the risk analyses further. GBanding karyotyping has been applied to the follow-up of radiation accident victims from the 1970s/80s, and many laboratories use the FISH technique to score translocations [25,26]. However, FISH has some uncertainties, such as adjustment for genome equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…However, a history of smoking was observed to have some effects on the chromosome translocation frequency [24]; follow-up studies of exposed subjects are needed to characterize the risk analyses further. GBanding karyotyping has been applied to the follow-up of radiation accident victims from the 1970s/80s, and many laboratories use the FISH technique to score translocations [25,26]. However, FISH has some uncertainties, such as adjustment for genome equivalence.…”
Section: Discussionmentioning
confidence: 99%
“…Радіоцезій є одним з небагатьох радіоізотопів (крім тритію та радіойоду у пацієнтів без щитоподібної залози), який у разі інкорпорації майже рівномірно розподіляється по тканинах організму [24, 103 -106]. Це надає можливість розробки цитогенетичних методів оцінки дози, обумовленого ним внутрішнього опромінення (на відміну від альфа-випромінюючих ізотопів та радіоізотопу 90 Sr).…”
Section: проблема цитогенетичної дозиметрії внутрішнього опромінення ...unclassified
“…Ефективність бета-частинок досліджена дуже мало і стосується в основному 3 H та 90 Sr [115 -123]. Так дослідження з використанням 90 Sr (за безпосереднього контакту клітин з радіоізотопом) показали, що можуть бути відмінності між бета-частинками та гамма-квантами в ефективності індукції пошкоджень ДНК [124] або хромосомних аберацій [118].…”
Section: проблема цитогенетичної дозиметрії внутрішнього опромінення ...unclassified
“…An ongoing task has been the search for a test that will estimate doses below 50 cGy accurately and reliably. Pilinskaya has shown that, among Ukrainian liquidators and children exposed environmentally to Chernobyl radionuclides, while there was not always a strong correlation between individual unstable chromosome aberration and individual physical dose estimates, there was a rather good correlation between average regional dose and average chromosome aberration [69]. FISH is a technique which is an extension of cytogenetic analysis [67,.…”
Section: Cytogenetic Biodosimetrymentioning
confidence: 99%